IMF Survey, Volume 35, Issue 02. (IMF Survey; IMF Survey ;, 2006)
De Rato in Brazil; Article IV summaries: Pakistan, Ukraine, CEMAC; Dawson on IMF's transparency revolution; Capital flight, institutions, and instability; Eastern Caribbean; Germany's regulation; Kazakhstan's non-oil sector; Trade, aid, and growth.